Prarancangan Pabrik Ammonia Dari Hidrokarbon Dan Udara Menggunakan Proses Kbr Dengan Disain Alat Utama High Temperature Shift Converter (R-104) - Fitri, Deyana Annisya; Fermi, Muhammad Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ammonia is raw material for fertilizer industry, refrigerant and textile. The need for ammonia is increasing due the development of the agricultural industry which uses ammonia as the main raw material. Ammonia is produced by reacting hydrogen from natural gas and nitrogen from air. This plant is designed to produce 350.000 ton ammonia per year, operated continuously for 330 days/year and 24 hours/day. The main of equipment design in this paper is high temperature shift converter (HTSC). In HTSC, carbon monoxide is converted into carbon dioxide with water and Fe-Cu catalyst for easier removal CO2 in the CO2 removal system. This reactor is operated at temperature 644oK and pressure 30 bar. Type of this rector is fixed bed multitube with 420 tube and cooling water in shell side. Fixed capital investment of this plant is Rp 1.237.828.356.614, total production cost Rp 1.441.431.713.805 and annual net profit Rp 988.881.802.274 From economical analysis, pay back period of this plant is 1,0102 year, return of investment 79,9% and break even point 20%. Keyword: Ammonia, Economic Analysis, Natural Gas, Reactor, Shift Converter